THE IMPLEMENTATION OF RESCHEDULING IN MURĀBAḤAH MICRO FINANCING AT BANK SYARIAH MANDIRI INDONESIA (An-Nisbah: Jurnal Ekonomi Syariah, 2019)
The Implementation of Rescheduling murābaḥah micro financing at Bank Syariah Mandiri Indonesia. This research is an analysis of the rescheduling of murābaḥah micro financing in Bank Syariah Mandiri Branch Dumai, Indonesia. There are many Shariah banks in Indonesia experiencing problems due to unpaid financing and can lower bank performance. Therefore, the bank is implementing the rescheduling of murābaḥah micro financing to avoid exceeding the level set by Bank Indonesia of 5%. This research was conducted to analyze in depth about the rescheduling of murābaḥah micro financing implemented by Bank Syariah Mandiri Branch Dumai, Indonesia. This research uses data collection method by observation, interview and library data which then analyzed by using inductive, deductive and comparative method. The result of this research is in the implementation of rescheduling the murābaḥah micro financing, there are three conditions, namely 1) not increasing the amount of remaining debt, 2) the costs in the rescheduling process are the actual costs, and 3) the additional payment time must be based on the agreement of both parties. From these conditions, the bank only does two, namely not increasing the amount of the remaining debt and adding payment time, while the bank is still wearing the customer with the rescheduling or penalty fees that make it difficult for the customer. Because of that, there are three suggestions from the researcher that is to provide a wide payment time, reschedule without the costs charged to the customer (penalty) except the actual costs such as administrative costs and conversion of murābaḥah financing contract into a qarḍ financing contract